Morphophysiological and biochemical recovery response of lettuce (Lactuca sativa L. var. Crispa) to multistress and the application of a phytohormone-based biostimulant - Satshi, Sanelisiwe (Central University of Technology, 2025)
Abiotic and biotic environmental stress factors are a threat to global food production. Abiotic stresses are the primary and leading factors constraining agricultural production, with an estimated annual reduction in crop yield of 70–80% globally. While the world population is expected to reach 9.7 billion by 2025, the agricultural sector continuously seeks creative approaches to boost production and resource efficiency to improve and maintain sustainable agricultural production to meet the food demands of the world population. In South Africa, lettuce (Lactuca sativa L.) is an economically important horticultural commodity with a diverse group of cultivars comprising different polymorphic characteristics and varying compositions of phytochemicals. It is consumed for its health benefits, such as minimising the risk of cardiovascular diseases, oxidative stress disorders, and colorectal cancer due to its high essential nutritional value and low calories and fats. Lettuce plants encounter complex interactions from multi-abiotic stresses. Two greenhouse experimental research trials were conducted using curly lettuce var. Crispa, during the October 2023 and June/July 2024 growing seasons at the Central University of Technology, Free State. Firstly, the study examined the effects of multi-abiotic stress, including water deficit, plant bag sizes, and mechanical wounding, on the morphophysiological and biochemical parameters of hydroponically grown curly lettuce. Secondly, the phytohormone-based biostimulant was evaluated on the morphophysiological and biochemical recovery response of curly lettuce grown under multi-abiotic stress conditions. The results in this study were obtained from ANOVA and multivariate analysis of unsupervised or supervised models, including PCAs, HCA cluster, OPLS-DA, PLS-DA, and VIP score plots. The first trial outcomes showed that water deficit, plant bag size, and mechanical wounding stress occurring individually or combined as multistress significantly decreased morphophysiological and biochemical parameters such as plant height, number of leaves, leaf area, chlorophyll contents, stomatal conductance and leaf mineral contents excluding the phenolic content, which was increased to combat the oxidative stress on plants. On the other hand, it was revealed from the second trial that the phytohormone-based biostimulant ameliorated the detrimental effects of mild, moderate, and severe abiotic stress conditions on plants and promoted the growth of plants under control conditions. However, the responses of plants were observed to be dependent on the intensity of the multistress condition and biostimulant application dose.
Master of Agriculture
Keywords: Lettuce; Horticultural plants; Abiotic stresses; Multistress; Water deficit; Plant bag size; Wounding; Biostimulants; Phytohormones